Analysis of Total Mangrove Carbon Stock Degradation in Kendari Bay. Issue 1 (March 2020) - Iswandi,; Helmi, M; Hadiyanto,
Abstract: Mangrove ecosystems are one of the blue carbon ecosystems in the coastal region. Mangroves can assimilate high carbon and can save carbon in the long term. Settlements and various centres of community activities have developed on the coast of Kendari Bay, which drastically decreased mangrove vegetation. Research on blue carbon placed in mangrove forests is vital to be carried out to determine changes in regional conditions in the coastal region. Spatial modelling is used to estimate the degradation of blue carbon stocks. A remote sensing data is required for producing spatial and temporal maps. InVEST (Integrated Assessment of Ecosystem Services and Sacrifices) can be used for mapping and modelling total carbon stock changes based on land cover changing in Kendari Bay. Carbon stocks can be calculated through spatial and temporal mapping in InVEST with past, present and future scenarios. Spatial dan temporal maps form InVEST can be considered in determining policies related to mangrove management and making more appropriate decisions in managing Kendari Bay area.